Enhancing ride-hailing adoption: understanding factors influencing ride-hailing user attitudes and reuse intention - Mudjahidin, Mudjahidin; Athallah, Rafid Ikbar (International Journal of Electrical and Computer Engineering (IJECE), 2026)
Ride-hailing applications (RHA) have emerged as a revolutionary force in the transportation landscape, offering convenient and on-demand mobility solutions, thus gaining widespread popularity in the transportation sector. However, concerns arise as many RHA startups find it difficult to survive in Indonesia, and even big RHA startups are still at risk. RHA must preserve user reuse intent in order to ensure service continuation. Based on the innovation diffusion theory (IDT), the unified theory of acceptance and use of technology (UTAUT), and additional factors, this study examines 11 variables and their impact on consumer attitudes and reuse intention in a model of ride-hailing service adoption. An online survey was utilized to gather data from various demographic backgrounds, and managed to gather data from 240 respondents. Analysis was conducted using partial least squares structural equation modeling (PLS-SEM) to assess the correlations between the variables. The findings revealed that perceived usefulness, perceived ease of use, perceived risk, compatibility, and personal innovation significantly influenced consumer attitudes. Additionally, it was shown that the attitude variable and customer reuse intention were positively and significantly correlated. Based on this outcome, recommendations were made to RHA providers to improve user attitudes and intentions to reuse.